2011
DOI: 10.1089/cap.2010.0054
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Uridine for Treatment of Depressed Adolescents with Bipolar Disorder

Abstract: This report is an open-label case series of seven depressed adolescents with bipolar disorder treated with uridine for 6 weeks. Treatment response was measured with the Children's Depression Rating Scale-Revised and the Clinical Global Impressions scale. Uridine was associated with decreased depressive symptoms, and was well tolerated by study participants. Further systematic studies of uridine are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Pyrimidine nucleosides, which include cytidine and uridine, constitute a class of molecules within the brain capable of impacting both energy metabolism and excitatory glutamatergic transmission, in addition to their role in the salvage pathway of pyrimidine nucleotide synthesis (Kondo et al, 2011). Cytidine and uridine have demonstrated antidepressant-like effects in studies conducted on rats completing the forced swim test (Carlezon et al, 2002(Carlezon et al, , 2005, as well as in patients with BD (Kondo et al, 2011;Yoon et al, 2009). It has been suggested that cytidine may exert neuroprotective effects by increasing cerebral high-energy phosphate levels and by reversing excess Glu neurotransmission (Hurtado et al, 2005;Radad, Gille, Xiaojing, Durany, & Rausch, 2007;Yoon et al, 2009).…”
Section: Pathway Analysismentioning
confidence: 99%
“…Pyrimidine nucleosides, which include cytidine and uridine, constitute a class of molecules within the brain capable of impacting both energy metabolism and excitatory glutamatergic transmission, in addition to their role in the salvage pathway of pyrimidine nucleotide synthesis (Kondo et al, 2011). Cytidine and uridine have demonstrated antidepressant-like effects in studies conducted on rats completing the forced swim test (Carlezon et al, 2002(Carlezon et al, , 2005, as well as in patients with BD (Kondo et al, 2011;Yoon et al, 2009). It has been suggested that cytidine may exert neuroprotective effects by increasing cerebral high-energy phosphate levels and by reversing excess Glu neurotransmission (Hurtado et al, 2005;Radad, Gille, Xiaojing, Durany, & Rausch, 2007;Yoon et al, 2009).…”
Section: Pathway Analysismentioning
confidence: 99%
“…metabolically recycled). Uridine supplementation has long been established as safe as long-term therapy of UMP synthase deficiency (13), but more recently it has been trialled in the treatment of adolescents with bipolar disorders (14).…”
Section: Uridine Therapymentioning
confidence: 99%
“…Uridine further provides a substrate in phosphatidylcholine (PC) synthesis [20][21][22]. It is understood that the mechanism of uridine in treating depression is via the cytidine 5 0 -diphosphocholine pathway which provides a critical substrate for phospholipid synthesis [23]. Primary research associated with uridine has demonstrated encouraging results as a possible antidepressant agent in analogue models with mice and also in improving symptoms of bipolar (depressive cycle) in children [21].…”
Section: Introductionmentioning
confidence: 99%
“…Primary research associated with uridine has demonstrated encouraging results as a possible antidepressant agent in analogue models with mice and also in improving symptoms of bipolar (depressive cycle) in children [21]. Uridine has also been shown to improve hippocampal metabolism and possibly raise dopamine levels [21,23]. While considered safe, uridine is both a complex and an expensive molecule for use in research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation